2021
DOI: 10.1371/journal.pone.0245325
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of different biomes drove the diversification of the Neotropical Eidmanacris crickets (Insecta: Orthoptera: Grylloidea: Phalangopsidae)

Abstract: The phylogeny of the cricket genus Eidmanacris is used to analyse its historical distribution and diversification in three South American biomes: Atlantic Forest, Cerrado, and Chiquitano Dry Forest. A morphological phylogeny with all the 29 species of Eidmanacris and the Geographically explicit Event Model (GEM) is used to explain their colonization and diversification through three different biomes and their ancestral habitats and distributional areas. We analysed ecologically-significant characters, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 88 publications
1
5
0
1
Order By: Relevance
“…The abovementioned explanations corroborate many studies indicating that the dry diagonal was a permeable barrier (due to several persistent patches of wet vegetation) that split the South American humid forests into the Amazon and Atlantic Forest (Johnson et al 1999, Redford & Fonseca 1986, Weisenberg & Mori 2020. The current distribution of many taxonomic groups, such as arachnids (Peres et al 2017), small mammals (Costa 2003, Redford & Fonseca 1986, birds (Silva 1996, Willis 1992), reptiles (Weisenberg & Mori 2020), anurans (Vasconcelos & Doro 2016), butterflies (Cabette et al 2017, Matos-Maraví et al 2021) and crickets (De Campos et al 2021) inside remnant humid forests along the dry diagonal is explained by this past separation of humid forests.…”
Section: The Atlantic Rainforests As a Source And Temporal Refuge Of ...supporting
confidence: 78%
See 1 more Smart Citation
“…The abovementioned explanations corroborate many studies indicating that the dry diagonal was a permeable barrier (due to several persistent patches of wet vegetation) that split the South American humid forests into the Amazon and Atlantic Forest (Johnson et al 1999, Redford & Fonseca 1986, Weisenberg & Mori 2020. The current distribution of many taxonomic groups, such as arachnids (Peres et al 2017), small mammals (Costa 2003, Redford & Fonseca 1986, birds (Silva 1996, Willis 1992), reptiles (Weisenberg & Mori 2020), anurans (Vasconcelos & Doro 2016), butterflies (Cabette et al 2017, Matos-Maraví et al 2021) and crickets (De Campos et al 2021) inside remnant humid forests along the dry diagonal is explained by this past separation of humid forests.…”
Section: The Atlantic Rainforests As a Source And Temporal Refuge Of ...supporting
confidence: 78%
“…Analysis in different temporal scenarios (21 ka, 6 ka, 0 ka and RCP8.5) based on the current Endecous distribution showed that these crickets almost did not reach the north of the Amazon biome. The same pattern was observed for the sympatric genus Eidmanacris Chopard, 1956(Castro-Souza et al 2020b, a group that is also dependent on remnants of humid forests and cave habitats (De Campos et al 2021). Although these two genera can co-occur inside caves, there is spatial segregation between their populations, with Endecous inhabiting deeper regions and Eidmanacris occurring near cave entrances, which would avoid competitive exclusion (Castro-Souza et al 2020b, Paixão et al 2017.…”
Section: The Atlantic Rainforests As a Source And Temporal Refuge Of ...mentioning
confidence: 72%
“…Other phylogenetic studies of crickets mostly focused either on limited geographical scales, or on limited ingroups, e.g. subfamily Gryllidae Eneopterinae (Vicente et al 2017 and references therein) or its tribes (Tan et al 2021), the Neotropical Phalangopsidae genus Eidmanacris Chopard, 1956(Campos et al 2021, the Hawaiian trigonidiine genus Nudilla Gorochov, 1988(Mendelson & Shaw, 2005, under the name Laupala Otte, 1994) or the eneopterine genus Cardiodactylus de Haan, 1844 (Dong et al 2018); He et al (2020), Shen et al (2020) and Ding et al (2021) studied the relationships of Chinese species of Trigonidiidae Trigonidiinae and Nemobiinae respectively. More recently, Campos et al (2022) studied the phylogeny of clade F of Chintauan-Marquier et al (2016), one of the two clades constitutive of the family Gryllidae, using both morphological and molecular characters in a worldwide perspective: these authors proposed to elevate clade F to family rank, i.e.…”
Section: A Cricket Phylogeny: a Reference Under Constructionmentioning
confidence: 99%
“…The results show differences in the degree of troglomorphism of the two subgenera, but it would be desirable to test these from precise phylogenies. In the case of crickets, although more and more work is being done on phylogenetic studies for different purposes [1,2,61,62,92,93], there are still few phylogenetic studies available to support these results. In addition, although their way of life has been updated, given the importance that the MSS is having in discovering in this environment, species previously linked only to caves, it is necessary to continue advancing in the knowledge about their way of life in order to have a more complete vision to face the issues discussed here.…”
Section: Troglomorphic Adaptationsmentioning
confidence: 99%